Porphyromonas gingivalis secretion leads to dysplasia of normal esophageal epithelial cells via the Sonic hedgehog pathway - Jia, Xueting; Liu, Jinan; He, Yinxue; Huang, Xiaofeng (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives To investigate the pathogenic effect of Porphyromonas gingivalis cultured media on the esophagus and the mechanism underlying the effect. Background Periodontitis is strongly associated with esophageal squamous cell carcinoma (ESCC). The cultured media of P. gingivalis may act on healthy esophagus to trigger a malignant transformation; however, this has not been confirmed. Methods Cell migration assays and cell cycle measurements were performed on normal human esophageal epithelial cells in the presence or absence of P. gingivalis cultured media. The esophagi of healthy adult C57BL/6J mice were isolated and cultured in-vitro. Hematoxylin-eosin and immunohistochemical staining using antibodies against proliferating cell nuclear antigen (PCNA), Claudin 1 and Claudin 4 were performed to detect dysplasia in specific tissues. Total mRNA was extracted to determine transcriptional dysregulation. A specific inhibitor of Sonic hedgehog signaling, cyclopamine, was used to confirm the underlying molecular mechanism. Results In the presence of P. gingivalis cultured media, proliferation and migration of normal human esophageal epithelial cells were up-regulated, and aneuploid cells appeared. Compared with control cells, the arrangement of mouse esophageal epithelial cells became disordered, the percentage of PCNA-positive cells increased, and the positive staining of Claudin 1 and Claudin 4 became weak. In addition, the expression of cancer-related pathway genes was up-regulated but tight junction-related gene expression was down-regulated. The Sonic hedgehog pathway was abnormally activated, and its inhibition reduced the pathogenic effect of P. gingivalis cultured media. Conclusions We revealed that the cultured media of the key periodontal pathogen, P. gingivalis, can induce the malignant transformation of normal esophageal epithelium through the Sonic hedgehog pathway.